Implementasi Project-Based Learning dalam Pembelajaran Fikih untuk Meningkatkan Pemahaman Siswa SDN 18/1 Teluk - Rofiqoh, Rofiqoh; Rofika, Rofika; Rutinah, Rutinah (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study aims to analyze the implementation of the Project-Based Learning (PjBL) model in Fiqh learning at SDN 18/1 Teluk and its impact on students' understanding. The application of PjBL in Fiqh learning is expected to increase students' active engagement and deepen their understanding of the Islamic religious concepts being taught. This research uses a classroom action research (CAR) method conducted in two cycles, involving observation, interviews, and student comprehension tests. The results indicate that the implementation of PjBL significantly improved students' understanding. In the first cycle, the average student score increased from 60 to 75, and in the second cycle, it rose to 85. Additionally, PjBL encouraged students to be more active, creative, and collaborative in the learning process. Despite some challenges, such as time management and task distribution within groups, PjBL proved effective in enhancing the quality of Fiqh learning. In conclusion, the PjBL model positively impacts students' understanding in Fiqh learning at SDN 18/1 Teluk.